Aplikasi Kecintaan dan Kebijaksanaan Ditinjau dari Filsafat - Operianus Mendrofa; Eka Periaman Zai; Indah Wijaya Lase; Samselinar Lase; Elisati Kurniawan Telaumbanua (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this research is to analyze the role and influence of philosophy in shaping an individual's character and maturity. This study employs a comprehensive literature review method to gather and evaluate various relevant resources. The results indicate that a profound understanding of philosophy serves not only as a tool for comprehending reality but also as a guide for making wise decisions in shaping an individual's perspectives on various issues, both in personal and social contexts. Through the application of philosophical principles, individuals can enhance their critical thinking skills, broaden their perspectives, and develop moral awareness. This study also emphasizes the importance of philosophy in education as a platform for building the character and ethics of the younger generation. The conclusion of this research is that philosophy plays a crucial role in strengthening an individual's love and wisdom, which in turn will have a positive impact on society as a whole. Therefore, it is essential for every individual to continue promoting the understanding and practice of philosophical principles in their daily lives. Keywords: Love, Wisdom, and Philosophy.